An Analysis of WhatsApp Interactions Among Youth: A Case of Language Attrition - Shubhra, Shubhra; Krishna, Devina (Journal of Digital Sociohumanities, 2024)
This study delves into the intriguing world of language dynamics within the popular messaging platform, WhatsApp, focusing on how young people communicate. Through the course of its research, this study aims to uncover a fascinating phenomenon called ‘Language Attrition’ - a subtle transformation in the way languages are used in this digital space. On WhatsApp, users seamlessly blend their native languages with a more global one. This results in a unique linguistic landscape where expressions from different languages coexist, sometimes making it challenging to distinguish between them. With India being a multilingual nation, the study explores the potential loss or degradation of languages due to the leniency and carelessness of social media language. The paper employs a mixed-method approach, combining qualitative analysis of WhatsApp conversations with a digital questionnaire survey. The research investigates factors such as the prevalence of emoticons, code-switching, and multilingualism, shedding light on the multifaceted dimensions of language attrition. The research investigates factors such as the prevalence of emoticons, code-switching, and multilingualism, shedding light on the multifaceted dimensions of language attrition. The insights aim to prompt one to perceive language attrition not merely as an academic curiosity but as a catalyst for proactive measures.